196k views
1 vote
3=x-3+5x

-117= -5(8x-8) +3

-3 = -4x+6-5x

Please help

User Piotr Duda
by
5.2k points

1 Answer

4 votes

Answer:

x = 1

x = 4

x = 1

Explanation:


\boxed{\begin{aligned}&\textsf{Given}: \quad & 3&=x-3+5x\\&\textsf{Combine terms in $x$}: \quad & 3&=6x-3\\&\textsf{Add 3 to both sides}: \quad &3+3&=6x-3+3\\&\textsf{Simplify}: \quad &6&=6x\\&\textsf{Divide both sides by 6}: \quad & (6)/(6)&=(6x)/(6)\\&\textsf{Simplify}: \quad& 1&=x\\&& x&=1\end{aligned}}


\boxed{\begin{aligned}&\textsf{Given}: \quad & -117 &= -5(8x-8) +3\\&\textsf{Distribute}: \quad & -117 &= -40x+40+3\\&\textsf{Simplify}: \quad & -117 &= -40x+43\\&\textsf{Subtract 43 from both sides}: \quad & -117-43 &= -40x+43-43\\&\textsf{Simplify}: \quad & -160 &= -40x\\&\textsf{Divide both sides by -40}: \quad & (-160)/(-40) &= (-40x)/(-40)\\&\textsf{Simplify}: \quad & 4&=x\\&&x&=4\end{aligned}}


\boxed{\begin{aligned}&\textsf{Given}: \quad & -3& = -4x+6-5x\\&\textsf{Combine terms in $x$}: \quad & -3& = -9x+6\\&\textsf{Subtract 6 from both sides}: \quad & -3-6& = -9x+6-6\\&\textsf{Simplify}: \quad & -9& = -9x\\&\textsf{Divide both sides by -9}: \quad & (-9)/(-9)& = (-9x)/(-9)\\&\textsf{Simplify}: \quad & 1&=x\\&&x&=1\end{aligned}}

User Cherif
by
6.1k points